Early intervention practices based on routines: A project for training and research | Práticas de intervenção precoce baseadas nas rotinas: Um projecto de formação e investigação - Isabel Chaves de Almeida (2011)
This article describes the work developed by the Grupo Técnico de Investigação (GTI), which resulted from a partnership between the Associação Nacional de Intervenção Precoce (ANIP) and different national universities with the scientific orientation of Professor Robin McWilliam. The aim of such partnership was to organize and implement a training course for Early Childhood Intervention (ECI) professionals designed to promote family centred routines based interventions. The conceptual framework underlying this training model is based on developmental-contextual theories, which sustain ECI practices embedded in everyday learning opportunities in natural environments. According to this perspective, McWilliam (2005) refers the concepts of engagement, independence and social relations, as well as four dimensions of the learning process in educational contexts, namely environment, activities, approach and interactions, and specifies how they can be used to plan intervention strategies that promote the quality of child interactions. The components of the training model are described, as well as subsequent research lines.